Geotechnical Suitability of Soils in Road Construction for Sustainable Development in Tropical Africa: Case of Lateritic Graveled Soils of Bandjoun (West, Cameroon) - Carlos Foko Tamba; Lucas Kengni; Paul Tematio (Advances in Civil Engineering)
The environmental impact of the exploitation of geomaterials and their relatively high cost, coupled with the increasingly low financial capital in developing countries, are pushing road actors to turn to inexpensive local ecological materials. The present study is conducted on lateritic graveled soils of Bandjoun (LGSB) in the West Cameroon Region. The aim is to determine whether lateritic gravel soils, particularly those in Bandjoun, can be an ecological and economical alternative to rock aggregates in road construction, considering their geotechnical parameters and environmental impact. These soils were described in the field and were also subjected to complete geotechnical identification in the laboratory. The LGSB presents Californian bearing ratio indices ranging from 26% to 83.3%, a plasticity index of 10.11%, a fines content of 12.05%, an average methylene blue value of 4.25, a water content at the Proctor optimum of 27.6% and a dry density of 1.75 g/cm3. They are silty or clayey gravels and sands of subgroup A-2-7 according to the Highway Research Board classification; sandy and gravelly soils with fines of class B according to the classification of the Road Construction Guide; and silty gravels according to the classification of the Central Laboratory of Bridges and Highways. These soils can be used naturally in pavement layers, in particular in subgrade for all traffic classes and in subbase for low traffic. The tonnage of these soils has been estimated at 18,389 t. The global warming index shows that the use of these soils (18,389 t) in road construction can reduce 31,629–62,706 kg of carbon emissions. The use of lateritic soils in road construction is a very interesting alternative to reduce the environmental impacts associated with the manufacture of rock aggregates. So, lateritic soils should be used instead of rock aggregates for cleaner, more environmentally friendly road construction. The present work presented a specific evaluation of the geotechnical properties and ecological impact of lateritic graveled soils for road construction, as well as their potential for ecological and economic utilization.